Microwave Assisted Hydrolysis of Holocellulose Catalyzed with Sulfonated Char Derived from Lignin-Rich Residue. (3rd September 2015) - Wang, Kui; Xie, Xinfeng; Si, Zhan; Jiang, Jianchun; Wang, Jingxin
Abstract : A microwave assisted green process has been developed for production of sugars through liquefying holocellulose catalyzed with sulfonated char derived from the lignin-rich residue produced during pretreatment of lignocellulose. Various reaction parameters including the hydrolysis temperature, hydrolysis time, catalyst content, and the ratio of water to feedstock were evaluated. The maximum sugars yield of 82.6% (based on the dry mass of holocellulose) was obtained under the optimum reaction conditions. The sulfonated char showed superior catalytic performance to that of dilute sulfuric acid in converting holocellulose into sugars under microwave irradiation.